2010
DOI: 10.5140/jass.2010.27.4.263
|View full text |Cite
|
Sign up to set email alerts
|

SW Lyncis-Advances and Questions

Abstract: DeceasedMany filtered CCD measures form the basis of six new light curves of the eclipsing system SW Lyn. From these measures and additional observations for eclipse timing, 47 new times of minimum light over the time-interval of about 13 years have been calculated. The complex period variability can be sorted into a linear period improvement with 5.8-year and 33.9-year periodic terms. The shorter cyclic term of these is ascribed to a cool companion of the eclipsing pair but the longer one has no testable inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Thus, PI3K-Akt signalling may activate downstream targets through pSTAT3 in NPY-or POMC-containing neurons (Sahu, 2011). The interaction between the dopaminergic system and leptin signalling in the hypothalamus is important in the control of energy homeostasis and treatment with dopamine D 2 receptor agonists and antagonists modulated leptin-induced food intake, STAT3 phosphorylation and nuclear trans-localization of pSTAT3 in the hypothalamus (Kim et al, 2010). In the present study, amphetamine, which is known to release dopamine, increased PI3K and pSTAT3 expression, a result similar to the action of leptin (Sahu, 2011).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, PI3K-Akt signalling may activate downstream targets through pSTAT3 in NPY-or POMC-containing neurons (Sahu, 2011). The interaction between the dopaminergic system and leptin signalling in the hypothalamus is important in the control of energy homeostasis and treatment with dopamine D 2 receptor agonists and antagonists modulated leptin-induced food intake, STAT3 phosphorylation and nuclear trans-localization of pSTAT3 in the hypothalamus (Kim et al, 2010). In the present study, amphetamine, which is known to release dopamine, increased PI3K and pSTAT3 expression, a result similar to the action of leptin (Sahu, 2011).…”
Section: Figurementioning
confidence: 99%
“…Dopamine regulates feeding via hypothalamic circuits in the brain and dopaminergic neurons project to the arcuate nucleus and to the median eminence in the hypothalamus. These neurons may influence the function of neuropeptide Y (NPY) and pro-opiomelanocortin (POMC) neurons involved in ingestive behaviours (Kuo, 2006;Kim et al, 2010; nomenclature follows Alexander et al, 2013). Dopamine may decrease NPY but increase POMC in the hypothalamus, resulting in decreased food intake in amphetamine-treated rats (Chen et al, 2001;Kuo et al, 2011;2012a).…”
Section: Introductionmentioning
confidence: 99%
“…These estimates may be used as preliminary values for further modeling using extended physical models based on the Wilson & Devinney (1971) code and it's extensions (Wilson 1979(Wilson , 1994(Wilson , 2012(Wilson , 2014Zola et al 1997Zola et al , 2010Bradstreet 2005;Kallrath et al, 2009;Linnel 2012;Reed 2012;Rucinski 2010;Prsa et al 2012). Such study of eclipsing binaries with the CBNU observations are reported by Jeong & Kim (2013); Kim & Jeong(2012); Jeong & Kim (2011) and Kim et al (2010a). It should be noted that the lack of spectral data doesn't allow to study various combination of stars in different evolutionary stages.…”
Section: Discussionmentioning
confidence: 98%
“…In their quest to find a plausible explanation the authors attempted to explain (among other possible explanations) the timing variations with a possible pair of light-travel time orbits corresponding to two circumbinary companions. In their discussion on the 34-year cycle Kim et al (2010) Irwin (1952). The minimum masses for the two companions is determined iteratively using the mass-function and are consistent with two separate Kepler orbits with the combined binary in one focus of the ellipse.…”
Section: Introductionmentioning
confidence: 99%
“…Because the 4th body orbit is circular (e2 = 0.0) the argument of pericenter (ω) and time of pericenter passage (T ) are undefined. Numbers in paranthesis denote the uncertainty of the last digit as adopted from Kim et al (2010). The mass of the primary and secondary components are 1.77 M⊙ and 0.92 M⊙, respectively.…”
Section: Introductionmentioning
confidence: 99%